Thermosetting polyurethane foam recycling method based on ethyl acetoacetate selective cracking biuret crosslinking point
By selectively pyrolyzing the biuret crosslinking points of polyurethane foam and combining it with photosensitive modification, the problems of high reagent consumption and low resource utilization in existing technologies have been solved, realizing efficient and economical recycling of polyurethane foam and preparing high-performance photocurable 3D printing resins and pressure-sensitive adhesives.
Patent Information
- Application Number
- CN202511391168.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-26
- Publication Date
- 2025-12-26
AI Technical Summary
Existing chemical depolymerization methods for recycling polyurethane foam suffer from problems such as high reagent consumption, high costs for separating and purifying depolymerization products, difficulty in utilizing isocyanate byproducts, and low performance and economic value of recycled products, resulting in the revenue from recycled products failing to cover the recycling costs.
High-performance photocurable 3D printing resin was prepared by selectively cleaving biuret crosslinking points with ethyl acetoacetate while retaining urethane and urea bonds in the non-crosslinked regions, and then grafting with a photosensitive reagent.
It reduces reagent consumption, simplifies the processing flow, and achieves 100% resource utilization of waste materials. The prepared recycled products have high added value and high performance, and are suitable for photopolymer 3D printing and pressure-sensitive adhesives.
Smart Images

Figure CN121203104A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of polyurethane foam recycling, and particularly relates to a thermosetting polyurethane foam recycling method based on selective cleavage of biuret crosslinking points of ethyl acetoacetate. BACKGROUND
[0002] Polyurethane foam is usually a porous polymer containing a large number of urethane bonds, urea bonds and biuret bonds in the molecule (the biuret bond has a crosslinking site function) formed by polymerization, foaming of polyisocyanate, polyol, water, etc. Polyurethane foam is widely used in mattresses, sofa cushions, car seat cushions, heat and sound insulation boards, etc. due to its excellent mechanical properties, processing properties, heat and sound insulation properties, and light weight, and has become an indispensable important synthetic material in life. However, its large-scale application will bring serious waste pollution problems at the end of its service life. Landfill and incineration methods not only cause resource waste, but also produce secondary pollution, which will harm the environment and human health.
[0003] Current recycling methods mainly include physical recycling method and chemical recycling method. Since polyurethane foam is mostly thermosetting material, its crosslinked network structure makes it insoluble and infusible, and cannot be reprocessed and utilized. Therefore, the current physical recycling method mainly crushes polyurethane waste and directly uses it as filler for new products. Although this method is simple to operate and low in cost, the regenerated product has poor performance and low economic value, which seriously limits its large-scale implementation. In contrast, the chemical depolymerization recycling method can open the urethane bond, urea bond and biuret bond in polyurethane through alcoholysis, ammonolysis and other ways, so as to degrade it into oligomer / small molecule compounds, such as Figure 1As shown in a, the obtained degradation products can be reused as raw materials for the synthesis of new materials, and the performance of the regenerated products can be comparable to that of the initial products, and the economic value is high. It is a promising technology path for high-quality recycling of waste polyurethane. However, the chemical depolymerization recycling method has the following problems at the present stage: (1) Large consumption of additional reagents (>70%, more than the proportion of waste materials). For example, the most studied and mature alcoholysis method, the current idea is to recover polyols from polyurethane by alcoholysis. However, the essence of this method is to "open all chemical bonds without distinction" formed during polymerization, which requires a large amount of degradation reagents and subsequent re-bonding reagents. Moreover, due to the high hydroxyl value of the recovered polyols, a large amount of fresh polyols need to be mixed during reuse, so the proportion of additional reagents in the regenerated product is usually much higher than that of waste materials. (2) The depolymerization products are a mixture of various oligomers and small molecule compounds, and the separation and purification cost is high. (3) Only part of the monomers (polyols) can be recycled and utilized, and the isocyanate by-product cannot be utilized, and the waste materials cannot be fully resourceful. (4) The recycling idea is usually closed-loop recycling, and the performance and economic added value of the regenerated product are not higher than those of the initial product. The above problems lead to the fact that the income of the regenerated product cannot cover its recycling cost, and even the more it is produced, the more it loses, which seriously hinders its large-scale application. The essential reason for this bottleneck is the lack of efficient and controllable chemical depolymerization and reuse technology. SUMMARY
[0004] To solve the above problems, the present application provides a method for recycling thermosetting polyurethane foam based on selective cleavage of biuret crosslinking points by ethyl acetoacetate. Ethyl acetoacetate is used as a depolymerization reagent, and the urethane bond / urea bond in the non-crosslinked region is preserved while the biuret bond crosslinking point in the polyurethane is selectively cleaved, thereby obtaining a polyol-isocyanate block depolymerization product. Then, through graft modification with a photosensitive reagent, a high-performance, high-value photocurable 3D printing resin is obtained.
[0005] To solve the above technical problems, the technical scheme adopted by the present application is as follows:
[0006] A method for recycling thermosetting polyurethane foam based on selective cleavage of biuret crosslinking points by ethyl acetoacetate, comprising the following steps:
[0007] 1) mixing polyurethane foam with ethyl acetoacetate and reacting to obtain a degradation solution;
[0008] 2) mixing the degradation solution obtained in step 1) with 2-isocyanate ethyl methacrylate, adding a photoinitiator to obtain a photocurable precursor;
[0009] 3) 3D printing the photocurable precursor obtained in step 2), and drying to obtain a regenerated 3D printing product.
[0010] Further, in step 1), the degradation temperature is 100-180℃, and the time is 10-300min.
[0011] Further, in step 1), the mass ratio of the polyurethane foam to the ethyl acetoacetate is 1:0.1-2.
[0012] Further, in step 1), after the reaction, the ethyl acetoacetate is separated and recycled.
[0013] Further, in step 1), the application of the obtained depolymerization product in a pressure-sensitive adhesive.
[0014] Further, in step 2), the mass ratio of the 2-isocyanate ethyl methacrylate to the polyurethane foam is 1-2:9.
[0015] Further, in step 2), the reaction temperature is 25-100℃, and the time is 20-300min.
[0016] Further, in step 2), the photoinitiator is selected from phenyl bis(2,4,6-trimethylbenzoyl) phosphine oxide, (2,4,6-trimethylbenzoyl) bis(p-tolyl) phosphine oxide, 2,4,6-trimethylbenzoyl-diphenyl phosphine oxide.
[0017] Further, in step 2), the mass of the photoinitiator accounts for 1%-3% of the total system.
[0018] Compared with the prior art, the present application has the following advantages:
[0019] (1) The reagent consumption of the present application is greatly reduced: the economy is the key to the promotion of the technology. The additional reagent of the existing method usually accounts for more than 70%, which is high in cost. The method of selective cleavage of biuret crosslinking points (while retaining the urethane bond / urea bond in the non-crosslinked region) in the present application can minimize the broken bond amount, and the additional reagent consumption can be reduced to 10%. This fundamentally reverses the dilemma of "economic unfeasibility" of the prior art, greatly reduces the raw material cost, and avoids the secondary resource waste in the recovery process itself.
[0020] (2) The process of the product of the present application is greatly simplified, and the waste can be 100% fully recycled: the depolymerization product of the prior art is a complex small molecule mixture, and the subsequent separation and purification process is complex and high in cost, and the isocyanate by-product is difficult to utilize. The product of the present application is an isocyanate-polyol block oligomer with similar structure, which is uniform in composition and can be directly used for reproduction without complex and expensive separation and purification steps, thereby simplifying the process and reducing the investment threshold; in addition, there is no isocyanate by-product, and the 100% recycling of waste polyurethane can be truly realized.
[0021] (3) The high value-added of the regenerated product of the present application: the large number of unbroken urethane bonds and urea bonds retained in the depolymerization product can serve as grafting / functioning sites, promoting the value-added reuse of the depolymerization product, so that it can be completely value-added into high-performance (high-elastic high-toughness), shape-reconfigurable high-value-added photocurable 3D printing products, and the economic value of the regenerated product is much higher than that of the existing chemical recycling method. BRIEF DESCRIPTION OF DRAWINGS
[0022] Figure 1 For comparison of the existing recycling technology and the recycling technology of the present application, figure a is the existing technology, and figure b is the technology of the present application;
[0023] Figure 2 The tensile stress-strain curve of the photocurable resin prepared in Examples 1-3 of the present application is shown in the figure;
[0024] Figure 3 The dynamic mechanical analysis (DMA) curve of the photocurable resin prepared in Examples 1-3 of the present application is shown in the figure;
[0025] Figure 4 The cyclic recovery curve of the photocurable resin prepared in Example 1 of the present application is shown in the figure;
[0026] Figure 5 The 3D printing product of the photocurable precursor liquid prepared in Examples 1-2 of the present application is shown in the figure, wherein figure a is the 3D printing product of Example 1, and figure b is the 3D printing product of Example 2;
[0027] Figure 6 The shape reconfiguration of the photocurable resin prepared in Example 1 is shown in the figure;
[0028] Figure 7 The application of the depolymerization product obtained in Examples 1-3 as pressure-sensitive adhesive is shown in the figure, wherein figures a-b are the adhesion schematic diagram of the depolymerization product to polytetrafluoroethylene, aluminum, paper and steel, figure c is the peeling test schematic diagram, figure d is the peeling strength diagram of the depolymerization product to polytetrafluoroethylene, aluminum, paper and steel, and figure e is the multiple cycle peeling strength diagram of the depolymerization product on steel. DETAILED DESCRIPTION
[0029] The present application will be further illustrated below in conjunction with specific examples, which are implemented on the premise of the technical solutions of the present application, and should be understood that these examples are only used to illustrate the present application and not to limit the scope of the present application.
[0030] The ethyl acetoacetate (EAA) used in the following examples was purchased from Macklin, the 2-isocyanate ethyl methacrylate (MAI) was purchased from Energy Chemical, the phenyl bis(2,4,6-trimethylbenzoyl) phosphine oxide was purchased from Aladdin, and the polyurethane foam was sourced from the production line of UE Furniture Co., Ltd.
[0031] Figure 1 A recycling method of thermosetting polyurethane foam based on selective cleavage of biuret crosslinking points of ethyl acetoacetate, comprising the following steps:
[0032] 1) mixing polyurethane foam with ethyl acetoacetate for reaction to obtain a degradation solution;
[0033] 2) mixing the degradation solution obtained in step 1) with 2-isocyanate ethyl methacrylate, adding a photoinitiator to obtain a photocuring precursor;
[0034] 3) 3D printing the photocuring precursor obtained in step 2), and obtaining a regenerated 3D printing product after drying.
[0035] Example 1
[0036] A recycling method of thermosetting polyurethane foam based on selective cleavage of biuret crosslinking points of ethyl acetoacetate, comprising the following steps:
[0037] (1) 4g of polyurethane foam was vacuum dried at 180℃ for 10min, then mixed with 4g of EAA, and reacted at 180℃ for 25min, the polyurethane foam was dissolved to form a uniform degradation solution.
[0038] (2) The degradation solution obtained in step (1) was mixed with 0.5g of MAI, and after reaction at 80℃ for 2h, phenyl bis(2,4,6-trimethylbenzoyl) phosphine oxide (1% of the total system mass) was added to obtain a photocuring precursor capped with acrylate derived from PUF.
[0039] (3) 3D printing was performed using a Miracle 3D-sla150ultra desktop 3D printer, with a layer thickness of 50μm, an exposure time of 30s per layer, and heating and drying to obtain a photocured 3D printing product.
[0040] Example 2
[0041] A recycling method of thermosetting polyurethane foam based on selective cleavage of biuret crosslinking points of ethyl acetoacetate, comprising the following steps:
[0042] (1) 4g of polyurethane foam was vacuum dried at 180℃ for 10min, then mixed with 4g of EAA, and reacted at 180℃ for 25min, the polyurethane foam was dissolved to form a uniform degradation solution. EAA was recovered by vacuum distillation, and polyurethane depolymerization product was obtained.
[0043] (2) The degradation product obtained in step (1) is mixed with 1.0 g of MAI, and after reacting at 80°C for 2 h, phenyl bis(2,4,6-trimethylbenzoyl) phosphine oxide (2% of the total system mass) is added to obtain a light-cured precursor capped with PUF-derived acrylate.
[0044] (3) 3D printing is performed using a Miracle 3D-sla150ultra desktop 3D printer, with a layer thickness of 50 μm and an exposure time of 30 s per layer, to obtain a light-cured 3D printed product.
[0045] Example 3
[0046] A method for recycling thermosetting polyurethane foam based on selective cleavage of biuret crosslinking points by ethyl acetoacetate, comprising the following steps:
[0047] (1) 4 g of polyurethane foam is vacuum dried at 180°C for 10 min, and then mixed with 4 g of EAA and reacted at 180°C for 25 min, so that the polyurethane foam is dissolved to form a uniform degradation solution. EAA is recovered by vacuum distillation, and a polyurethane depolymerization product is obtained.
[0048] (2) The degradation product obtained in step (1) is mixed with 2.0 g of MAI, and after reacting at 80°C for 2 h, phenyl bis(2,4,6-trimethylbenzoyl) phosphine oxide (3% of the total system mass) is added to obtain a light-cured precursor capped with PUF-derived acrylate.
[0049] (3) 3D printing is performed using a Miracle 3D-sla150ultra desktop 3D printer, with a layer thickness of 50 μm and an exposure time of 30 s per layer, to obtain a light-cured 3D printed product.
[0050] Performance test of the regenerated light-cured 3D printed product of Examples 1-3:
[0051] The tensile test results of the light-cured resin prepared in Examples 1-3 show that Figure 2 when the PUF dosage is 67%, the tensile strength of the regenerated product is 21.37 ± 1.87 MPa, the elongation at break is 75.28 ± 4.18%, the elastic modulus is 135.16 ± 26.9 MPa, and the toughness is 12.19 ± 1.16 MJ·m -3When the PUF content increased to 80% and 89%, the tensile strength decreased to 11.76±0.35 MPa and 7.72±1.11 MPa, respectively, but significantly improved the elongation at break (197.69±12.63% for the 80% PUF sample and 513.37±114.48% for the 89% PUF sample) and toughness (13.98±0.96 MJ·m for the 80% PUF sample). -3 The 89% PUF sample had a concentration of 19.75 ± 5.63 MJ·m⁻¹. -3 More importantly, its elastic modulus can be adjusted to 23.63±0.28MPa (80% PUF sample) and 2.24±0.18MPa (89% PUF sample), respectively, which can better meet the needs of flexible material applications.
[0052] The dynamic thermomechanical analysis (DMA) test results of the photocurable resins prepared in Examples 1-3 show that ( Figure 3 The flexible polyether segments in the recycled PUF have extremely low glass transition temperatures around -40°C, giving the material excellent flexibility at room temperature.
[0053] The cyclic tensile test results of the photocurable resin prepared in Example 1 show that ( Figure 4 Recycled products have excellent resilience.
[0054] Figure 5 The photocurable 3D printed products based on polyurethane waste prepared in Examples 1 and 2 are shown.
[0055] Shape reconfigurability studies show that recycled resin can be repeatedly reshaped into different geometries without the need for predefined molds; this can be achieved simply by heat treatment at 100°C under applied deformation loads. Figure 6 As shown, after the recycled product is heated and shaped, it can be transformed from a planar two-dimensional film into a three-dimensional structure with curls and patterns.
[0056] Example 4
[0057] The intermediate depolymerization products obtained in Examples 1-3, in addition to being used to manufacture the aforementioned photopolymerizable 3D printed products, can also be used as pressure-sensitive adhesives (PSA) for tapes, bandages, and sticky notes. They possess temporary adhesive capabilities through rapid and low-strength bonding; their adhesion does not require heating or light radiation equipment, but can be activated simply by manual pressing at room temperature. Figure 7 As shown, through 100mm 2 The depolymerized PUF product was manually scraped onto the surface area. PUF-based PSA can adhere to all test substrates, including steel, aluminum foil, paper, and Teflon. Figure 7a-b). Peel tests showed that the PUF-based PSAs had peel strengths of 30.0 ± 8.3 N / m, 9.5 ± 2.2 N / m, 10.9 ± 1.0 N / m, and 5.6 ± 1.2 N / m for steel, aluminum foil, paper, and polytetrafluoroethylene, respectively Figure 7 c-d). In addition, the PUF-based PSAs also exhibited excellent re-adhesion ability and reusability, with no significant decrease in peel strength after three "stick-peel" cycles Figure 7 e).
[0058] The above only is the preferred embodiment of the present application, it should be pointed out that, for those skilled in the art, without departing from the principles of the present application, can also make a number of improvements and refinements, these improvements and refinements should also be considered as the protection scope of the present application.
Claims
1. A method for recycling thermoset polyurethane foams based on the selective cleavage of biuret crosslinks by ethyl acetoacetate, characterized by: The method comprises the following steps: 1) mixing polyurethane foam with ethyl acetoacetate to react, to obtain a degradation solution; 2) mixing the degradation solution obtained in step 1) with 2-isocyanatoethyl methacrylate, and adding a photoinitiator, to obtain a photocuring precursor; 3) 3D printing the photocuring precursor obtained in step 2), and drying to obtain a regenerated 3D printing product.
2. The thermoset polyurethane foam recycling method based on selective cleavage of biuret crosslinks by ethyl acetoacetate of claim 1, characterized in that: In step 1), the degradation temperature is 100-180℃, and the time is 10-300min.
3. The thermoset polyurethane foam recycling method based on selective cleavage of biuret crosslinks by ethyl acetoacetate of claim 1, characterized in that: In step 1), the mass ratio of polyurethane foam to ethyl acetoacetate is 1:0.1-2.
4. The thermoset polyurethane foam recycling method based on selective cleavage of biuret crosslinks by ethyl acetoacetate of claim 1, characterized in that: In step 1), after the reaction, the ethyl acetoacetate is separated and recycled.
5. The thermoset polyurethane foam recycling method based on selective cleavage of biuret crosslinks by ethyl acetoacetate of claim 1, characterized in that: In step 1), the application of the depolymerization product obtained in a pressure-sensitive adhesive.
6. The thermoset polyurethane foam recycling method based on selective cleavage of biuret crosslinks by ethyl acetoacetate of claim 1, characterized in that: In step 2), the mass ratio of 2-isocyanatoethyl methacrylate to polyurethane foam is 1-2:
9.
7. The thermoset polyurethane foam recycling method based on selective cleavage of biuret crosslinks by ethyl acetoacetate of claim 1, characterized in that: In step 2), the reaction temperature is 25-100℃, and the time is 20-300min.
8. The thermoset polyurethane foam recycling method based on selective cleavage of biuret crosslinks by ethyl acetoacetate of claim 1, characterized by: In step 2), the photoinitiator is selected from phenyl bis(2,4,6-trimethylbenzoyl) phosphine oxide, (2,4,6-trimethylbenzoyl) bis(p-tolyl) phosphine oxide, and 2,4,6-trimethylbenzoyl-diphenyl phosphine oxide.
9. The thermoset polyurethane foam recycling method based on selective cleavage of biuret crosslinks by ethyl acetoacetate of claim 1, characterized in that: In step 2), the mass of the photoinitiator accounts for 1%-3% of the total system mass.